The chopped moving photocarrier grating technique - Kopprio, Leonardo Hugo (2019)
The Moving photocarrier Grating Technique (MGT) allows the simultaneous determination of the photocarrier drift mobilities and the small-signal recombination lifetime of photoconductive semiconductors. The technique measures the direct current (DC) induced by a monochromatic illumination consisting of a moving interference pattern superimposed on a uniform background of much higher intensity. A drawback of the technique is the low level of the signal to be measured, which can be masked by the noise at low temperatures or low light intensities. In this work, we propose implementing an alternating current (AC) version of the MGT by chopping the weak beam in the standard configuration. We call this new technique the Chopped Moving photocarrier Grating (CMG). In CMG, the AC signal can be measured with a lock-in amplifier for electrical noise removal. In this way, the signal-to-noise ratio can be increased compared to the standard DC technique. Assuming a multiple-trapping model for charge transport, we find the theoretical expression for the current density induced by CMG at fundamental frequency. By using a numerical simulation with parameters typical for hydrogenated amorphous silicon, we verify the expected equivalence between both techniques for low enough chopping frequencies. Then, we test experimentally this equivalence for an undoped hydrogenated amorphous silicon sample. For low signal levels, we demonstrate the superior performance of CMG.